Love will follow: why the Indian marriage is burning - Sandhya, Shaifali (New Delhi, 2009)
This book is about the conflicted state of marriage in India today. With economic growth, middle-class Indians are experiencing stark changes from the ones experienced by their grandparents and parents. The Indian marriage is burning. In this groundbreaking study the first clinical and cultural portrait of its kind-Dr Shaifali Sandhya explores the intimate lives of middle class Indian husbands and wives living in India and abroad and looks at what is causing this breakdown. Interviewing countless couples, using current research, and looking deeply at the key areas in relationships which cause conflict-sex, money, family-she draws a devastating picture of the modern Indian marriage. Hardhitting, eyeopening, and completely riveting, Love will Follow takes you into the hearts and minds of Indian men and women. Full of moving stories, fascinating statistics, and insights, it could change the way you see your relationship-and your life.
Keywords: Husband and wifes-Indian middle class